The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1063/1.4807578
|View full text |Cite
|
Sign up to set email alerts
|

Transport properties and electrical device characteristics with the TiMeS computational platform: Application in silicon nanowires

Abstract: Nanoelectronics requires the development of a priori technology evaluation for materials and device design that takes into account quantum physical effects and the explicit chemical nature at the atomic scale. Here, we present a cross-platform quantum transport computation tool. Using first-principles electronic structure, it allows for flexible and efficient calculations of materials transport properties and realistic device simulations to extract current-voltage and transfer characteristics. We apply this co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 51 publications
(87 reference statements)
0
17
0
Order By: Relevance
“…We performed electron transport calculations by means of the NEGF extension of the OpenMX code, 29 which is by now widely used. [38][39][40][41][42][43] The model implemented in this software makes use of periodic boundary conditions. The basis sets employed consist of linear combinations of atomic orbitals generated by a confinement scheme which yields wave functions with zero value beyond a chosen cutoff radius.…”
Section: Methodsmentioning
confidence: 99%
“…We performed electron transport calculations by means of the NEGF extension of the OpenMX code, 29 which is by now widely used. [38][39][40][41][42][43] The model implemented in this software makes use of periodic boundary conditions. The basis sets employed consist of linear combinations of atomic orbitals generated by a confinement scheme which yields wave functions with zero value beyond a chosen cutoff radius.…”
Section: Methodsmentioning
confidence: 99%
“…All calculations used a grid spacing of 0.6 a 0 , giving Hamiltonian dimensions N from 13,000 to 22,000. Also shown are reference calculations using the TIMES transport code 45 to compute T (E) in the linear response regime based on OpenMX 46 electronic structure. The OpenMX calculation used a basis set of 17 orbitals per atom for both the hydrogen and carbon chains.…”
Section: A Atomic Chain Testsmentioning
confidence: 99%
“…It is found that six layers of Au atoms (3 repeat units) form an electrode cell that is sufficiently large to make nextnearest-neighbour interactions between cells negligible. This model of the junction and semi-infinite electrodes are then used with the TiMeS quantum transport program [31] to calculate electron transmission. The TiMeS program uses semi-analytical expressions for the Green's functions in the NEGF formalism for which the limit for the artificial broadening parameter approaching zero has been taken.…”
Section: Methodsmentioning
confidence: 99%